2014
DOI: 10.1182/blood-2013-12-541953
|View full text |Cite
|
Sign up to set email alerts
|

Nordic MCL3 study: 90Y-ibritumomab-tiuxetan added to BEAM/C in non-CR patients before transplant in mantle cell lymphoma

Abstract: Y-ibritumomab-tiuxetan (Zevalin) to the highdose regimen. One hundred sixty untreated, stage II-IV mantle cell lymphoma patients <66 years received rituximab (R)-maxi-CHOP (cyclophosphamide, hydroxydaunorubicin, vincristine, and prednisone) alternating with R-high-dose cytarabine (6 cycles total), followed by high-dose BEAM/C (bis-chloroethylnitrosourea, etoposide, cytarabine, and melphalan or cyclophosphamide) and autologous stem cell transplantation from 2005 to 2009. Zevalin (0.4 mCi/kg) was given to respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 31 publications
4
73
1
Order By: Relevance
“…Similarly, in the Nordic MCL3 study, 25 MRD status after ASCT was strongly prognostic for PFS, with 4-year PFS of about 38% (median PFS,~3 years) in 18 patients who had MRD-positive PB or BM compared with about 88% in 89 MRD-negative patients. The prognostic value of MRD status after ASCT was stronger than that before ASCT and was also seen after adjustment for MIPI, Ki-67 index, computed tomography status before ASCT and positron emission tomography (PET) status before ASCT, with adjusted HRs of 5.0 for PFS and 4.8 for OS.…”
Section: Predictive Value Of Mrd In Clinical Remission After Treatmentmentioning
confidence: 80%
See 3 more Smart Citations
“…Similarly, in the Nordic MCL3 study, 25 MRD status after ASCT was strongly prognostic for PFS, with 4-year PFS of about 38% (median PFS,~3 years) in 18 patients who had MRD-positive PB or BM compared with about 88% in 89 MRD-negative patients. The prognostic value of MRD status after ASCT was stronger than that before ASCT and was also seen after adjustment for MIPI, Ki-67 index, computed tomography status before ASCT and positron emission tomography (PET) status before ASCT, with adjusted HRs of 5.0 for PFS and 4.8 for OS.…”
Section: Predictive Value Of Mrd In Clinical Remission After Treatmentmentioning
confidence: 80%
“…In the Nordic MCL3 study, similar to the MCL Younger trial, 53% molecular remissions were observed by qualitative nested PCR in patients with clinical remission after 5 alternating R-CHOP/R-HA cycles. 25 The investigation of MRD during induction treatment indicates that the higher intensity of modern regimens is reflected in a rapid tumor cell clearance in PB and BM. Therefore, MRD assessment seems to be well suited for precisely monitoring the impact of different treatment schemes or individual drugs on tumor cell clearance.…”
Section: Mrd During and After Induction Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2006, several studies have described promising results in relapsed or refractory NHLs with heterogeneous cohorts including iNHLs but also a majority of aggressive lymphomas. [1][2][3][4][5] Only one phase II prospective study in indolent lymphomas showed a benefit of 90 YIT in association with BEAM (Z-BEAM) as intensive therapy. 6 There is a lack of data about the efficacy and safety of Z-BEAM conditioning regimen in iNHLs especially because of short follow-up in the published data.…”
mentioning
confidence: 99%